Evaluating the Vocabulary Test - Nia Pujiawati (Universitas Mathla'ul Anwar Banten, 2015)
This study describes the analysis of vocabulary test given to the students seen from the difficulty level (ID) and discriminating power (DP) point of view and also from reliability and validity judgment. This vocabulary test was conducted at SDN Puseurjaya, an elementary school located at Karawang, from January 30th 2012 through February 1st 2012. After doing the analysis on the items, it was found that the test of vocabulary given to the second grade of SDN Puseurjaya students meets almost all requirements to be the acceptable test items. However, as it does not reach validity, the writer then needs to check and review in depth to make some improvements for the next test construction.